Randomized controlled trial of emotion-focused training for helping professionals - Halamová, Júlia; Ondrejková, Natália; Kováč, Karol (Frontiers in Psychology, 2022)
The aim of this study was to examine the short- and long-term effectiveness of the novel Emotion-focused Training for Helping Professions on levels of compassion fatigue (secondary traumatic stress & burnout), self-criticism, self-compassion, and compassion for others. A randomized controlled trial study was conducted. A total of 253 participants were recruited and randomly assigned to either the experimental group or the control group. The experimental group attended a 14-day online training. The control group did not perform any tasks. Results showed that after completing the intervention the experimental group participants reported significantly lower scores for secondary traumatic stress, burnout and self-criticism, and higher scores for self-compassion and that these lasted for two months after completion. Compared to the control group, the experimental group participants had significantly lower scores of secondary traumatic stress, burnout, self-criticism, and higher scores of self-compassion after the intervention. No significant changes were found for the control group, except a significant increase in time in the reported score for one dimension of burnout – exhaustion. The novel EFT-HP training was shown to be effective in reducing levels of compassion fatigue (secondary traumatic stress and burnout) and self-criticism and increasing self-compassion.